2023
DOI: 10.3390/ijerph20031934
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Low-Cost Sensor Networks at Detecting Fine-Scale Variations in Particulate Matter in Urban Environments

Abstract: The negative health impacts of air pollution are well documented. Not as well-documented, however, is how particulate matter varies at the hyper-local scale, and the role that proximal sources play in influencing neighborhood-scale patterns. We examined PM2.5 variations in one airshed within Indianapolis (Indianapolis, IN, USA) by utilizing data from 25 active PurpleAir (PA) sensors involving citizen scientists who hosted all but one unit (the control), as well as one EPA monitor. PA sensors report live measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 49 publications
0
4
0
1
Order By: Relevance
“…More recent studies have found such SES variables as income, education, housing, and ethnic groups to result in increased outdoor PM concentrations [4][5][6][7][8][9][10][11]. However, even with the advent of low-cost monitors, none of these studies were able to show an effect on indoor concentrations [12][13][14][15][16]. In the present study, we aim to use one of the largest studies employing low-cost monitors to explore the effect of smoking on indoor concentrations of more than 4000 residents of three West coast states.…”
Section: Environmental Justicementioning
confidence: 99%
“…More recent studies have found such SES variables as income, education, housing, and ethnic groups to result in increased outdoor PM concentrations [4][5][6][7][8][9][10][11]. However, even with the advent of low-cost monitors, none of these studies were able to show an effect on indoor concentrations [12][13][14][15][16]. In the present study, we aim to use one of the largest studies employing low-cost monitors to explore the effect of smoking on indoor concentrations of more than 4000 residents of three West coast states.…”
Section: Environmental Justicementioning
confidence: 99%
“…A study in Texas found that counting re-suspended dust emissions as part of PM 2.5 emissions could increase concentration readings by between 50 to 75 percent [22]. A study in Indianapolis that used low cost sensors found a negative correlation between PM 2.5 and tree canopy percentage, and a positive correlation with PM 2.5 and heavy industry [23]. Temporal and meteorological associations may also play an important role in PM 2.5 levels and deserve to be better understood, as they have been found to be potentially complex and multifaceted in nature.…”
Section: Literature Surveymentioning
confidence: 99%
“…This is in contrast to the stationary EPA monitors. Low-cost sensors have already been used in many studies, allowing for citizen scientists to conduct research and measure small-scale air quality variations [23].…”
Section: Literature Surveymentioning
confidence: 99%
“…De igual forma, el estudio de (Heintzelman et al, 2023) logró determinar que, con el uso de dispositivos electrónicos, sensores a tiempo real conocidos como Purple Air (PA), ubicado en 25 sitios de Indianápolis, Estados Unidos, se determinó que al elevar en 1% los dispositivos PA hacia las copas de los árboles, se disminuye en un ~0,12 g/m 3 en PM2,5; mientras que al elevar la proximidad de dichos sensores a áreas de 'industria pesada', los niveles de contaminación se incrementan en 0,07 g/m 3 en PM2,5. Estos resultados refuerzan la relevancia de este tipo de sensores a tiempo real,y el uso de las tecnologías convergentes a fin de apoyar esfuerzos para la caracterización y control de contaminación.…”
Section: Tecnologías Convergentes Para Caracterización De Contaminant...unclassified